Avaliação agronômica e nutricional de quatro genótipos de milheto em quatro estádios - Diego Soares Goncalves Cruz (2013)
This study was carried out to evaluate the agronomic traits, nutritional value and in vitro fermentation kinetics of whole plant and leaf and stem fractions of pearl millet genotypes BRS 1501, CMS 1, CMS and J 3 1188 at four stages of maturity. Genotype BRS 1501 was taller than the other at 72 days of maturity (P<0.05), and genotype J 1188 was the lowest (P<0.05). Genotype BRS 1501 stand was superior to the other genotypes (P<0.05), which did not differ among than (P>0.05), being observed a linear decrease because of the advance in maturity stage. The wet matter yield varied between 30.8 and 41.35 t/ha and showed a linear decrease as a function of the cut time, however the genotypes did not differ (P>0.05). The dry matter yield genotype BRS 1501 was superior to genotype CMS 1 (P<0.05). Genotype CMS 1 showed lower digestible dry matter yield than the other (P<0.05), how did not differ among than. Leaf/stem ratio did not differ between genotypes (P>0.05), and decreased linearly with age. The BRS 1501 genotype showed whole plant dry matter superior to the other materials (P<0.05). All fractions of the plant showed a linear increase in dry matter with age. No differences were found for levels of mineral contents among genotypes in whole plant, stems and leaves (P>0.05). Whole plant crude protein were similar for the all genotypes (P>0.05), ranging between 10.52 and 11.41%. Neutral detergent fiber content of all fractions of the plant did not differ between genotypes (P>0.05). Genotype CMS 1 had higher levels of acid detergent fiber in whole plant fraction than genotype J 1188 (P<0.05). Lignins content of whole plant fraction did not differ between the genotypes (P<0.05). The J 1188 genotype showed digestible dry matter in vitro of whole plant higher than CMS 1 genotype (P<0.05). The genotype BRS 1501 stood out with the lowest values of lag time. Gas production by fibrous carbohydrates fermentation (Vf2) was greater than no fibrous carbohydrates fermentation (Vf1). No difference between genotypes for dry matter disappearence values (P>0.05). According to results, pearl millet can be used in diets for ruminants with lower nutritional requirements. Genotypes BRS 1501 highlighted by higher dry matter yield and shorter lag time during fermentation than the others.